2023
DOI: 10.1186/s12944-023-01792-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum growth differentiation factor-15 and non-esterified fatty acid levels in patients with coronary artery disease and hyperuricemia

Abstract: Background High serum NEFA and GDF-15 are risk factors for CAD and have been linked to detrimental cardiovascular events. It has been hypothesized that hyperuricemia causes CAD via the oxidative metabolism and inflammation. The current study sought to clarify the relationship between serum GDF-15/NEFA and CAD in individuals with hyperuricemia. Methods Blood samples collected from 350 male patients with hyperuricemia(191 patients without CAD and 159… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Molecular signals produced using oxidative stress, insulin resistance, endothelial dysfunction, or the inflammatory response allow hyperuricemia to stimulate the onset and progression of CAD and increase the risk of mortality and morbidity from CAD. Cheng et al have shown a positive correlation between GDF-15 levels and CAD in male patients with hyperuricemia [42]. They found that GDF-15 concentrations were correlated with uric acid, and GDF-15 levels were higher in male hyperuricemia patients suffering from CAD than in those with hyperuricemia alone.…”
Section: Discussionmentioning
confidence: 97%
“…Molecular signals produced using oxidative stress, insulin resistance, endothelial dysfunction, or the inflammatory response allow hyperuricemia to stimulate the onset and progression of CAD and increase the risk of mortality and morbidity from CAD. Cheng et al have shown a positive correlation between GDF-15 levels and CAD in male patients with hyperuricemia [42]. They found that GDF-15 concentrations were correlated with uric acid, and GDF-15 levels were higher in male hyperuricemia patients suffering from CAD than in those with hyperuricemia alone.…”
Section: Discussionmentioning
confidence: 97%